Framework of National Architectural Identity of Public Administration Buildings: A Case Study of Majlis Bandaraya Johor Bahru (MBJB) Tower - Rahmat, Muhamad Hanafi; Ismail, Alice Sabrina; Mandala, Ari Ani (International Journal of Sustainable Construction Engineering and Technology, 2022)
In the context of a multi-racial country consisting of Malays, Chinese, and Indians as the main majority, the search for the value of national architectural identity is important in highlighting racial harmony. Therefore, establishing the national architectural identity framework is necessary to ensure this can be realized. This paper focuses on the construction of an architectural framework of national identity based on the results of previous scholarly studies. This study uses a hermeneutic methodology in which data were collected from scholarly views through literature reviews and then interpreted into its disciplinary subject matter in compiling the indicators for the national architectural identity to propose a framework for public administration building in Malaysia. A case study of green building certified –MBJB Tower is used to further broaden the understanding of the national identity of architecture in Malaysia. An interview session with related personnel and site observation was carried away at MBJB Tower to test the proposed framework. An interpretive paradigm was used to explore each architectural element of national identity and a narrative method was used to discuss the findings in this paper. As an outcome, the architectural framework of the national architectural identity of public administration buildings consists of an understanding of the role, typology, and themes of architectural national identity. The architectural design pattern of national identity for public buildings is seen at three levels, namely macro, meso and micro levels. The architectural measurement of the national identity of a building can be defined by the design features produced based on the context of venustas, firmitas, and utilitas. In general, the MBJB Tower building is a good example of national identity architecture and can be used as a benchmark to produce more national architectural identity buildings in the future.